2015
DOI: 10.1007/s00221-014-4188-2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental tests of hypotheses for microsaccade generation

Abstract: Fixational eye movements such as microsaccades are important to prevent fading. These miniature eye movements are also necessary to redirect gaze to the target after a drift. Generation of saccades and microsaccades utilizes common neural substrates. We, therefore, hypothesized that physiological modulators of saccades should also affect microsaccades. Test of this hypothesis will also provide support for the models of a microsaccade generation. We performed two experiments. In the first experiment, complete d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Therefore, the definition of microsaccades that we used for this study could potentially include both microsaccades and small-amplitude saccades. The eye movement data were converted to degrees and filtered using a Savitsky-Golay filter with an order of 3 and a frame length of 41 (Cherici, Kuang, Poletti, & Rucci, 2012;Ghasia & Shaikh, 2015;Ko, Snodderly, & Poletti, 2016). The filtered eye movement data were used for further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the definition of microsaccades that we used for this study could potentially include both microsaccades and small-amplitude saccades. The eye movement data were converted to degrees and filtered using a Savitsky-Golay filter with an order of 3 and a frame length of 41 (Cherici, Kuang, Poletti, & Rucci, 2012;Ghasia & Shaikh, 2015;Ko, Snodderly, & Poletti, 2016). The filtered eye movement data were used for further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The visual cortex signals microsaccade production while the superior colliculus drives such input to generate microsaccades. [40][41][42] Therefore, visual cortical impairment likely affects the physiology of subcortically generated microsaccades. Studies have shown that during fixation, amblyopes have decreased microsaccade production.…”
Section: Discussionmentioning
confidence: 99%
“…We then normalized the proportion of microsaccades in a given bin to the size of the population. Such normalization allowed comparison of the distributions without being affected by uneven sample size [20]. Normalized occurrence of microsaccades is plotted on the y -axis while corresponding bin value is plotted on the x -axis.…”
Section: Resultsmentioning
confidence: 99%
“…In order to exclude visually guided or voluntary saccade, we used saccades that did not accompany target shifts and were smaller than 4° amplitude. The variables of interest were as follows: amplitudes, intersaccadic invervals, peak velocities, and drift velocities and variance in eye position during intersaccadic interval; data analysis was performed using custom-prepared software in Matlab ™ programming language [20]. Further analysis was performed in three steps.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation